SOSIALISASI PENGGUNAAN DIGIFASCH (DIGItal FASter CHarity) : APLIKASI PENGUMPULAN MODAL PELAKU UMKM TERDAMPAK GEMPA BUMI CIANJUR - Hanisa Sismaya Lestari; Endah Lisarini; Asep Saepul Alam; Desi Dwi Jayanti; M. Yahya Ahmad (LPPM Universitas Bina Bangsa, 2024)
Community service was carried out for 12 MSMEs affected by the earthquake. These 12 MSMEs were selected from the selection results from Benjot and Sarampad Villages. The aim of this activity is to assist MSMEs affected by the Cianjur earthquake which occurred in 2022. As a result of this earthquake, many MSMEs have had their businesses stopped due to limited capital. So far, government assistance has focused on providing food after the earthquake, but has not focused on capital assistance to continue business. The community service carried out by lecturers and students at the Faculty of Applied Science, Suryakancana University, focuses on mentoring, followed by socialization on how to use fundraising applications, from creating an account to creating a campaign, which was delivered to 24 accompanying students who for 5 months accompanied MSMEs to take part in 20 mentoring sessions. and finally closed with the activity of distributing donations to each MSME